2012
DOI: 10.2527/jas.2011-3902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 1-stage and 2-stage selection in yellow perch I: Genetic and phenotypic parameters for body weight of F1 fish reared in ponds using microsatellite parentage assignment1

Abstract: Two selection methods, 1-stage selection (OSS) and 2-stage selection (TSS), for improving efficiency and profitability of selective breeding of yellow perch were evaluated, through examining the genetic and phenotypic parameters for BW of F(1) fish using microsatellite parentage assignment in this study. Approximately 94% of the sampled yellow perch progeny were assigned to single parental pairs using 8 microsatellite markers, which confirmed the applicability of the communal rearing technique in yellow perch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Many researchers reported that unequal family sizes could also result in some bias in the estimates of the genetic parameters (Fishback et al . ; Wang, Lo, Zhu, Lin, Feng, Li, Yang, Tan, Chou, Lim, Orban & Yue ; Cao, Wang, Yao, O'Bryant, Rapp, Wang & MacDonald ). On the contrary, Sae‐Lim, Komen and Kause () found that REML was robust against unbalanced design in their simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers reported that unequal family sizes could also result in some bias in the estimates of the genetic parameters (Fishback et al . ; Wang, Lo, Zhu, Lin, Feng, Li, Yang, Tan, Chou, Lim, Orban & Yue ; Cao, Wang, Yao, O'Bryant, Rapp, Wang & MacDonald ). On the contrary, Sae‐Lim, Komen and Kause () found that REML was robust against unbalanced design in their simulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, female BW during breeding season is increased due to the larger volume of gonads (Cao et al . ), and therefore BL can be a better indication of meat yield than BW in some instances. In this sense, Friars et al .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, microsatellite-based parentage identification approach could be a better alternative to overcome these defects imposed by physical tags as it can be retrospectively used after the growth phase of fish has been evaluated. It has been demonstrated that the accuracy of parentage assignment was usually very high even estimated with few microsatellite loci (Castro et al 2007;Gheyas et al 2009;Cao et al 2012). In this study for golden mandarin fish, performed with seven microsatellite loci, the allocation success rate was 91.6 % in parentage identification with known parental and filial information and 89.5 % in pedigree analysis in mixed families.…”
Section: Discussionmentioning
confidence: 82%
“…This allowed different progeny groups to be reared communally after hatching and retrospectively assigned to their original families without requirement of physical tagging or separate rearing for the progeny before stocking into the ponds. To date, it has been demonstrated that microsatellites were a very useful tool to determinate parentage, analyze pedigree and identify species in many studies (Chan et al 2003;Cao et al 2012;Moghim et al 2013;Sourinejad et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The results from the MCMC Bayesian and REML analysis were varied in all traits in this study, and this might be caused by different tolerances of the whole sample size, unequal family sizes, and common environmental factors in different models and analyses. Although REML is thought to be robust against unbalanced design in their simulation (Sae‐Lim et al ), more research of environmental factors, unequal family sizes, and sample size could result in some bias in the estimates of the genetic parameters (Falconer and Mackay ; Fishback et al ; Wang et al ; Cao et al ). Although the heritabilities were different between the two methods, all the growth traits were moderate to high heritabilites, as has been the case in the other fish species (Fishback et al ; Liu et al ) and also in our previous studies of M. amblycephala (Luo et al ; Zeng et al ).…”
Section: Discussionmentioning
confidence: 99%